Separation and identification of some toxins from Centruroides margaritatus venom (Gervais,1841) (Scorpiones : Buthidae) - Escobar, Enrique (2003)
Proteins of Centruroides margaritatus scorpion venom had been separated by cationic exchange chromatography in CM-Sephadex C-25 with 0,05M ammonium acetate pH 7, from 28,3 mg of venom obtained from 52 adults scorpions caught in Zarumilla, Tumbes, north of Peru. The chromatographic elution showed 9 protein peaks and toxicity assays allowed the identification of three toxins with specific activity on crustacean, insects and rodents, respectively. Both the crude venom and the collected fractions have shown neither phospholipase nor proteoyitic activity. The PAGE-SDS of crude venom shows one very notorious protein band of 14 kDa aproximately, and another two thin bands of 45 kDa aproximately, which imply that the majority of proteins from this venom are of a molecular weight similar or less than 14kDa.